Assembly of supertetrahedral clusters into a Cu–In–S superlattice via an unprecedented vertex–edge connection mode. Issue 32 (3rd August 2017) - Wang, Hongxiang; Yang, Huajun; Wang, Wei; Xue, Chaozhuang; Zhang, Yingying; Luo, Min; Hu, Dandan; Lin, Jian; Li, Dongsheng; Wu, Tao
Abstract : We demonstrated the first case of a vertex–edge inter-cluster connection mode in a three-dimensional open-framework chalcogenide built from the largest known T5 cluster. Abstract : We demonstrated here the first case of a vertex–edge connection mode in a three-dimensional open-framework chalcogenide built from the largest known T5 cluster. Such connection relies on a tri-coordinated edge sulfur atom, which serves as the linkage to bridge two adjacent T5 clusters. The architecture of the resulting structure can be classified as the infinite order of super-supertetrahedral T5 clusters (T5, ∞).